FRAGMENTS OF OCEANIC ISLAND IN THE KURAI AND KATUN' ACCRETIONARY WEDGES OF GORNY ALTAI - Dobretsov N.L.; Buslov M.M.; Safonova I.Yu.; Kokh D.A. (My University, 2004)
The paper presents new data on the structure and composition of the Vendian-Early Cambrian oceanic crust of the Paleo-Asian ocean, which has been fragmentally preserved in Early Cambrian accretionary prisms of Gorny Altai. Mid-ocean ridge and oceanic island basalts have been recognized based on their geochemical characteristics and the composition and geological relationships of volcanogenic and sedimentary units. Our data indicate that hot-spot and mid-ocean ridge volcanism was active at the early stages of the Paleo-Asian ocean evolution, in the period from Vendian to Early Cambrian. The study of paleo-oceanic islands incorporated in accretionary-collisional belts is important for the reconstruction of ancient oceans and understanding of endogenic processes that led to the formation of the oceanic lithosphere.
Keywords: Vendian-Cambrian; oceanic crust; Paleo-Asian ocean; MORB; OIB; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский; Paleozoic::Cambrian; Палеозой::Кембрийская